1979
DOI: 10.1038/hdy.1979.89
|View full text |Cite
|
Sign up to set email alerts
|

Ecological adaptations in Douglas-fir (Pseudotsuga menziesii var. glauca) populations

Abstract: SUMMARYGrowth, phenology and frost tolerance of seedlings from 50 populations of Douglas-fir (Pseadotsuga men ziesli var. glauca) were compared in 12 environments.Statistical analyses of six variables (bud burst, bud set, 3-year height, spring and fall frost injuries, and deviation from regression of 3-year height on 2-year height) showed that populations not only differed in mean performance, but also reacted differently to the environmental gradient. Most of the populationenvironment interaction was attribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
2
1

Year Published

1982
1982
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 14 publications
3
48
2
1
Order By: Relevance
“…Regression model 1 (table 2) indicated that (1) genetic variation was related to elevation; (2) geographic patterns of variation followed a grid that was oblique to latitude and longitude; and (3) habitat types were related to neither dependent nor independent variables. A lack of association between habitat types and genetic variation in western Montana corresponds with results for Douglas-fir populations from northern Idaho (Rehfeldt 1979a) and for Pinus ponderosa from southern Idaho (Rehfeldt 1980). …”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…Regression model 1 (table 2) indicated that (1) genetic variation was related to elevation; (2) geographic patterns of variation followed a grid that was oblique to latitude and longitude; and (3) habitat types were related to neither dependent nor independent variables. A lack of association between habitat types and genetic variation in western Montana corresponds with results for Douglas-fir populations from northern Idaho (Rehfeldt 1979a) and for Pinus ponderosa from southern Idaho (Rehfeldt 1980). …”
Section: Resultssupporting
confidence: 70%
“…Interactions of genotype and environment were detected for only bud burst and height. While accounting for little variance, these interactions, like those detected for north Idaho populations (Rehfeldt 1979a), resulted from mean differences not associated with changes in the ranking of populations.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…An alternative to extensive, long-term field testing is to map patterns of genetic variation in the native stand from short-term tests at a single site (Campbell 1986, Langlet 1945, Rehfeldt 1983, Squillace 1966. Two main assumptions are implicit if genetic maps are used to devise provisional zones: (1) genetic variation among populations reflects natural selection by an environment that varies across locations; and (2) the greater the genetic difference among populations, the greater the risk in transfers of seedlings between origins of populations.…”
Section: Introductionmentioning
confidence: 99%